Tunable Terahertz Absorption with Optical Tamm State in the Graphene-Bragg Reflector Configuration - Shuai Wang; Guimei Li; Yanhong Zou (Advances in Condensed Matter Physics)
Tunable terahertz absorption in the interface between graphene and dielectric Bragg reflector (DBR) has been numerically demonstrated. The near perfect absorption mainly originates from the enhancement of the electric field owing to the excitation of the optical Tamm state (OTS) at the interface between graphene and dielectric Bragg mirror. It has been found that the absorption peak occurs at specific incident angles, which can be employed for realizing the frequency and angular absorbers. Further, we demonstrate that the position of the absorption peak can be tuned by changing the Fermi energy of graphene. Moreover, the behaviors of the near perfect absorption are strongly related to the dielectric constants and thicknesses of the surrounding dielectrics. The tunability of graphene-DBR structure absorption may help to find favorable applications for the realization of high-performance graphene optoelectronic devices.